METACOHORTS for the study of vascular disease and its contribution to cognitive decline and neurodegeneration: An initiative of the Joint Programme for Neurodegenerative Disease Research. Issue 12 (1st August 2016) - ,; Dichgans, Martin; Wardlaw, Joanna; Smith, Eric; Zietemann, Vera; Seshadri, Sudha; Sachdev, Perminder; Biessels, Geert Jan; Fazekas, Franz; Benavente, Oscar; Pantoni, Leonardo; De Leeuw, Frank‐Erik; et al.
Abstract: Dementia is a global problem and major target for health care providers. Although up to 45% of cases are primarily or partly due to cerebrovascular disease, little is known of these mechanisms or treatments because most dementia research still focuses on pure Alzheimer's disease. An improved understanding of the vascular contributions to neurodegeneration and dementia, particularly by small vessel disease, is hampered by imprecise data, including the incidence and prevalence of symptomatic and clinically "silent" cerebrovascular disease, long‐term outcomes (cognitive, stroke, or functional), and risk factors. New large collaborative studies with long follow‐up are expensive and time consuming, yet substantial data to advance the field are available. In an initiative funded by the Joint Programme for Neurodegenerative Disease Research, 55 international experts surveyed and assessed available data, starting with European cohorts, to promote data sharing to advance understanding of how vascular disease affects brain structure and function, optimize methods for cerebrovascular disease in neurodegeneration research, and focus future research on gaps in knowledge. Here, we summarize the results and recommendations from this initiative. We identified data from over 90 studies, including over 660, 000 participants, many being additional to neurodegeneration data initiatives. The enthusiastic response means that cohorts from North America, Australasia, and the Asia Pacific Region are included, creating a truly global, collaborative, data sharing platform, linked to major national dementia initiatives. Furthermore, the revised World Health Organization International Classification of Diseases version 11 should facilitate recognition of vascular‐related brain damage by creating one category for all cerebrovascular disease presentations and thus accelerate identification of targets for dementia prevention.